Peningkatan Kesadaran Pendidikan Tinggi melalui Kolaborasi Perguruan Tinggi: Implementasi Aplikasi 'Jamali Parenting' di Desa Jamali, Cianjur : Increasing Higher Education Awareness through Higher Education Collaboration: Implementation of the 'Jamali Parenting' Application in Jamali Village Cianjur - Fitrianingsih, Fitrianingsih; Saryoko, Andi; Elyana, Instianti; Aziz, Faruq; Ramadhan, Aditya Rian; Supriyono, Lawrence Adi; Andini, Siwi Putri; Budiyanto, Sarah Khairunnisa; Daryati, Elisabeth Isti; Wadu, Novita M Kana; Erna, Maria Agustina; Dwiyogo, Santos Winarso; Saeda, Ida (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
This Community Service Activity is a collaboration of five universities under the auspices of LLDIKTI III, namely Gunadarma University, Nusa Mandiri University, Jakarta International University, Esa Unggul University, and STIK Sint Carolus. This activity aims to increase public awareness of the importance of higher education in building the future of the golden generation. The event was held on Monday, December 9, 2024, at the Jamali Village Hall, Mande District, Cianjur Regency, West Java, with the partner of the Head of Jamali Village, Mr. Cece Rusman, S.IP. Activities include outreach regarding parenting patterns for child growth and development and the importance of higher education as the key to the future of the golden generation. In addition to education, this activity resulted in an innovation in the form of the "Jamali Parenting" application, which is designed to support the management of information and education programs for village communities. The implementation method includes delivering educational materials, interactive discussions, and training in using the application. The results of the activity showed public enthusiasm for the importance of higher education as well as positive acceptance of the "Jamali Parenting" application. This application is expected to be a tool to improve the quality of education and information in Jamali Village. This activity reflects the synergy between universities and the community in realizing a common goal, namely to produce a superior and competitive generation. With this collaboration, it is hoped that a wider awareness will be created about the strategic role of higher education in creating a better future. ABSTRAK Kegiatan Pengabdian kepada Masyarakat ini merupakan kolaborasi lima perguruan tinggi di bawah naungan LLDIKTI III, yaitu Universitas Gunadarma, Universitas Nusa Mandiri, Universitas Jakarta Internasional, Universitas Esa Unggul, dan STIK Sint Carolus. Kegiatan ini bertujuan untuk meningkatkan kesadaran masyarakat tentang pentingnya pendidikan tinggi dalam membangun masa depan generasi emas. Acara dilaksanakan pada Senin, 9 Desember 2024, di Balai Desa Jamali, Kecamatan Mande, Kabupaten Cianjur, Jawa Barat, dengan mitra Kepala Desa Jamali, Bapak Cece Rusman, S.IP.  Kegiatan meliputi sosialisasi mengenai pola asuh tumbuh kembang anak dan pentingnya Pendidikan Tinggi sebagai kunci masa depan generasi emas. Selain edukasi, kegiatan ini menghasilkan inovasi berupa aplikasi Jamali Parenting yang dirancang untuk mendukung pengelolaan informasi dan program pendidikan masyarakat desa. Metode pelaksanaan meliputi penyampaian materi edukasi, diskusi interaktif, dan pelatihan penggunaan aplikasi. Hasil kegiatan menunjukkan antusiasme masyarakat terhadap pentingnya pendidikan tinggi serta penerimaan positif terhadap aplikasi Jamali Parenting. Aplikasi ini diharapkan menjadi alat bantu dalam meningkatkan kualitas pendidikan dan informasi di Desa Jamali.  Kegiatan ini mencerminkan sinergi antara perguruan tinggi dan masyarakat dalam mewujudkan tujuan bersama, yaitu mencetak generasi yang unggul dan berdaya saing. Dengan kolaborasi ini, diharapkan tercipta kesadaran yang lebih luas tentang peran strategis pendidikan tinggi dalam menciptakan masa depan yang lebih baik.